1972
DOI: 10.1080/00335557243000102
|View full text |Cite
|
Sign up to set email alerts
|

On the Division of Attention: A Disproof of the Single Channel Hypothesis

Abstract: In dichotic listening, subjects are apparently unable to attend simultaneously to two concurrent, auditory speech messages. However, in two experiments reported here, it is shown that people can attend to and repeat back continuous speech at the same time as taking in complex, unrelated visual scenes, or even while sightreading piano music. In both cases performance with divided attention was very good, and in the case of sight-reading was as good as with undivided attention. There was little or no effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
253
2
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(288 citation statements)
references
References 23 publications
23
253
2
3
Order By: Relevance
“…To do this, you have to keep task-switching (one moment speaking, the next moment listening). Yet, we know that in general multi-tasking and task switching are really challenging [2]. Try writing a letter while listening to someone talking to you!…”
Section: Problems Posed By Dialoguementioning
confidence: 99%
“…To do this, you have to keep task-switching (one moment speaking, the next moment listening). Yet, we know that in general multi-tasking and task switching are really challenging [2]. Try writing a letter while listening to someone talking to you!…”
Section: Problems Posed By Dialoguementioning
confidence: 99%
“…Several experiments have demonstrated such effects (e.g. Allport, Antonis, & Reynolds 1972;Schumacher, et al 1997). EPIC predicts that perfect time-sharing is possible where there is a lack of input interference (e.g.…”
Section: Perfect Time-sharingmentioning
confidence: 99%
“…For example, Allport, Antonis, and Reynolds (1972) found that people could attend to and repeat (shadow) continuous auditory speech while processing unrelated visual scenes or sightreading piano music. Additional work indicated that while shadowing, if participants were presented with a series of words to remember, recall was worse if the words were presented in auditory rather than visual mode.…”
Section: Modality Effectsmentioning
confidence: 99%